1990
DOI: 10.1901/jaba.1990.23-431
|View full text |Cite
|
Sign up to set email alerts
|

Self‐administered Written Prompts to Teach Home Accident Prevention Skills to Adults With Brain Injuries

Abstract: This study evaluated the use of written checklists and task analyses as self-administered prompts to teach home accident prevention skills to 4 adults with brain injuries. Subsequent to baseline, participants used written checklists that identified potential in-home hazards but did not prompt behaviors necessary for hazard remediation. Written individualized task analyses, incorporating specific behavioral steps for correcting hazards that participants had failed to remediate during the checklist phase, were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Daily activities. Three studies were found describing strategies specifically aimed at improving the performance of daily activities (57)(58)(59). No overall strategies could be identified as the studies used widely differing interventions, namely checklist training, the use of an assistive technology device and the use of mental imagery of daily tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Daily activities. Three studies were found describing strategies specifically aimed at improving the performance of daily activities (57)(58)(59). No overall strategies could be identified as the studies used widely differing interventions, namely checklist training, the use of an assistive technology device and the use of mental imagery of daily tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The literature in cognitive rehabilitation for brain injury patients demonstrates that the use of self-administered checklists and individualized task analyses as prompts, helped patients avoid common hazards at home (e.g safely putting away a space heater) and to continue independent activities (e.g. cooking) (17). …”
Section: Cognitive and Behavioral Symptomsmentioning
confidence: 99%
“…The strategy effectively reduced the frequency of aggressive and challenging behaviors but these improvements were not maintained once the cues were withdrawn. Other strategies have included the use of token economies [77], verbal contracts [78], reinforcement and informational feedback [79], initial reduction of task demands [80], caregiver education [81], stress inoculation training [82], extinction [83], and home-based mentoring [84]. All these intervention strategies have demonstrated success in treating post-TBI behavior problems.…”
Section: Emotional Social and Behavioral Interventionsmentioning
confidence: 99%